Strengthening Community-Based Environmental Security through Digital Technology in Ciganitri Village, Bandung Regency - Dhea Kusuma Wardhani; Rafi Dewantara Rachmat; I Kadek Nuary Trisnawan; Cheyza Amanda Syafira; Monica Febyana; Agung Nugroho Jati; Surya Michrandi Nasution (CogniSpectra Publishing, 2026)
Background: Environmental security is essential for residential safety and quality of life. In RW 10, Kp. Ciganitri, Lengkong Village, Bojongsoang District, Bandung Regency, the existing conventional surveillance system has several blind spots, contributing to several theft incidents and estimated economic losses of approximately IDR 35,000,000. This community service program aims to strengthen community-based environmental security by integrating digital technology and citizen empowerment. Contribution: This program contributes to the community by strengthening environmental security, enhancing residents’ capacity to manage digital security technology, and fostering active community participation. Method: A participatory and collaborative approach was adopted involving residents and RW administrators. The program included blind-spot mapping, CCTV installation at strategic locations, integration of a remote monitoring system, preparation of standard operating procedures (SOPs), resident training, the establishment of a community security monitoring group, followed by monitoring and evaluation. Results: Four outdoor IP CCTV units were installed at strategic points (main gate, main road, and parking area) with standalone local storage, cloud backup, and real-time remote monitoring via a mobile application. A community security monitoring group was formed and residents were trained in system operation and incident reporting. A satisfaction survey of 20 residents showed that 100% agreed or strongly agreed that the program met community needs, was well implemented, and should be continued.. Conclusion: The integration of digitally-based CCTV with community empowerment effectively strengthened environmental security in RW 10, closing surveillance blind spots and increasing residents' sense of safety, while supporting SDG 9 and SDG 11 and providing a replicable model for other community-based digital security initiatives.